Mieszanie cieczy wysokolepkich. Podstawy procesowe - Kuncewicz, Czesław (Wydawnictwo Politechniki Łódzkiej, 2012)
Based on years of industrial experience and laboratory tests, it was found that highly viscous liquids such as molten polymers, pastes, bitumen, varnishes, pulps, dyestuffs, resins, tar etc. are best mixed by close-clearance agitators, i.e. ribbon, horseshoe and screw impellers operating in a diffuser. Slightly less popular solutions in this case appeared to be frame, scrape and screw agitators operating without a diffuser. Among the above listed types of agitators ribbon and screw impellers deserve the most attention. While working, they produce high secondary circulation practically in the whole mixer irrespective of the viscosity of liquid being stirred. High radial and axial circulation causes also that just the last two types of impellers are most popular in practical applications. This monograph presents a discussion of the state of experimental investigations and theoretical studies on close-clearance impellers operating in laminar motion. A separate problem discussed in the book is modeling of mixer hydrodynamics and heat transfer for the impellers. The monograph consists of segments. In the first two chapters the fundamental notions of primary and secondary circulation in the mixer, the function of current, current lines, circulation time, etc. used further in the book are defined. The main properties of liquid as a continuous species are discussed there. The three subsequent chapters present a discussion of helical ribbon, horseshoe and screw impellers. Every impeller type is considered from the point of view of the analysis of hydrodynamics of a mixer-impeller system, mixing time, heat transfer coefficients, mixing power and efficiency. Depending on the impeller type, the center of gravity of the presented analysis is shifted towards this region in which the given impeller type is most frequently applied. The book presents numerous tables containing dimensionless or semi-empirical equations proposed by various authors to calculate many basic values. The tables have been critically evaluated. Opposite to turbulent flow, mixing of highly viscous liquids proceeds always in the laminar or deeply laminar regime which is often called the creeping flow. Very often, highly viscous liquids are not non-Newtonian liquids. Thus, there are problems associated with the necessity of taking into account the whole spectrum of non-Newtonian liquids and with the analysis of mixing efficiency with respect to energy consumption. High liquid viscosity causes that much energy is required to drive the impeller. This is directly proportional to the viscosity of liquid. Hence, for each type of the impeller methods to determine mean shear rates of liquid in the mixer and to calculate apparent viscosity of non-Newtonian liquid have been described. Because there are many types of non-Newtonian liquids, the book is focused only on shear-thinned and viscoelastic liquids. The last chapter of the monograph is dedicated to modeling of the mixer hydrodynamics in laminar motion. This is a reference to modem and still more popular methods associated with the application of CFD techniques which help the designing process. In this chapter attention is focused on discussing various authors' models available in the literature rather than on the discussion of integrated packages accessible on the market. Discussion of the latter ones can easily be found in the scientific and commercial literature. The presented monograph is intended for students of higher years of studies at the departments of chemical engineering, chemistry, mechanical engineering and related ones. The monograph should be particularly helpful for students preparing their diploma theses, providing them with appropriate literature on the subject and for PhD students in the above mentioned departments. Besides being helpful for students, the book can also be useful for designers who cope in their professional work with the problems of mixing highly viscous liquids. At present, there are no universal methods to select properly the type and geometric parameters of an impeller according to the main goal of mixing, viscosity of the liquid being mixed and its rheological properties.
Red. serii Monografie : Wodziński, Piotr
Keywords: mieszanie - modele matematyczne; ciecze - właściwości mechaniczne; mieszanie - aparatura i sprzęt; płyny nienewtonowskie - mieszanie; przepływ płynu lepkiego - badania; mixing - mathematical models; liquids - mechanical properties; mixing - apparatus and equipment; non-Newtonian fluids - mixing; viscous fluid flow - testing